Lexical bundles in psychology lectures and textbooks: a contrastive corpus-based study with implications for academic writing - Alasmary, Abdullah (Frontiers in Psychology, 2025)
Research on lexical bundles (LBs) has explored various academic domains; however, the field of psychology has received comparatively less attention. This study aims to address this gap by contrastively investigating the use of LBs in two sub-corpora: videotaped lectures and textbook chapters. Four-word bundles that meet a predetermined set of selection criteria are elicited and subsequently analyzed both structurally and functionally. The results indicate significant variation in the number of bundle types and tokens between the two registers, with the spoken register exhibiting a much broader variety of LBs than the written register. Structural analysis reveals that clausal constructions predominantly characterize LBs in the spoken psychology register, whereas phrasal patterns are more common in the written register. Additionally, the functional analysis highlights that stance bundles constitute the most prevalent category in the academic lecture corpus, while referential bundles emerge as the largest functional category in the academic texts. This variation reinforces the widely accepted notion that LBs are sensitive to register differences. Pedagogically, the study provides English for Specific Purposes instructors with data-based lists of LBs that can be integrated into classroom activities or tailored to develop instructional materials on academic writing and speech. Given that LBs are classified into distinct structural and functional groups, moreover, instructors can draw on the two lists for more register-focused, awareness-raising activities that help psychology students approximate an expert-like writing style.